Avaliação de políticas públicas para alfabetização: formação do professor alfabetizador, concepção e aplicação da Provinha Brasil - Rosário, Mônica Maria Soares (2012)
The results of the National High School Examination (ENEM) and the National Assessment of Basic Education (SAEB) – large-scale assessment systems, through the which the Brazilian government evaluates school education – and the Program for Evaluation International Student Association (PISA) – an international system with the same purpose – demonstrate that the school has not been performing its function of forming competent readers, nor has Cultivated a regular reading routine among young people. What could be the causes of this failure? Perhaps the answer lies in children's literacy. Along these lines, the Federal Government began to apply the Provinha Brasil – an instrument for diagnosing the level of literacy – in the 2nd year of Brazilian public schools, since 2008; such an examination, in the long term, may improve the reading performance of Brazilians. This dissertation aims to verify whether the literacy teacher training and prior knowledge of the document lead the student to achieve success in the Brazilian Prov. For that, we follow two applications of Provinha Brazil, carried out in a school in the municipal network of Aracaju, in 2010, to check if the teacher follows the guidelines contained in the Teacher/Applicator Notebook and what is the training profile of this professional. In the bibliographic stage, we investigated the linguistic conceptions that guide the Provinha Brasil, to compare with the contents presented in the menus and subject programs of the Pedagogy courses in the state (training institutions for literacy teachers). We found that these courses have a curriculum that does not converge with the theories that guide the Provinha Brasil. Such discrepancy can influence the application of the test and, more importantly, the orientation of the results obtained. Another factor identified in the analysis of the application was the lack of a reading preview of the material by the literacy teacher, since many instructions are not followed by the professor or transmitted by him to the students, compromising the verisimilitude of collecting the results. And, in the interviews carried out with the teachers, we found the fear of these professionals to have their teaching practice in the condition of literacy teachers evaluated according to the results of these tests. These results suggest remodeling of the educational structure, with guidelines for the curricular readjustment of the courses of training of literacy teachers and carrying out training for test-administering teachers.